Rhodium-Catalyzed Aryl Migratory/Decarbonylation of Diaryl Ketones via the Activation of Unstrained C–C Bonds - Yu, Tian-Yang; Lu, Hong; Shao, Peng-Cheng; Qi, Xiu-Juan; Wei, Hao (Synthesis, 2021)
A Rh-catalyzed aryl migratory/decarbonylation of unstrained ketones has been developed. This viable transformation provides a complementary decarbonylative method using diaryl ketones to afford a variety of alkenylated heterocycles in good yields with moderate to good stereoselectivity and broad substrate scope. The synthetic utility of this protocol is also demonstrated by the conversion of the alkenylated heterocycles to tetrahydrocarbazole derivatives.
Keywords: aryl migration; decarbonylation; unstrained ketones; Rh-catalysis; alkenylated heterocycles